Giant Popliteal Artery Aneurysm: Case Report and Review of the Literature - Christos Verikokos; Georgios Karaolanis; Mikes Doulaptsis; Georgios Kouvelos; Aikaterini Kotzadimitriou; Viktoria-Varvara Palla; Christos Klonaris (Case Reports in Vascular Medicine)
Popliteal artery aneurysms (PAAs) are rare in general population but represent the second most common peripheral arterial aneurysms following those located in the aortoiliac segment. They usually affect men over 60 years old with established cardiovascular disease caused by atherosclerosis. Other more unusual conditions such as trauma, congenital popliteal aneurysm, mycotic aneurysm, inflammatory arteritis, or popliteal entrapment are responsible. The authors report the first ever case of a male diagnosed with chronic renal failure with giant popliteal artery aneurysm. We have successfully resected the aneurysm and revascularized with synthetic graft.